TekenToken Development: IoT based Cartesian Robot System for Prepaid Electricity Token Recharging Automation - Puji, Muhammad Nurul; Eduard, Christoper; Fico (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2025)
Manual input of the prepaid token on the electricity meter is prone to several drawbacks, such as the possibility of entering incorrect numbers or dealing with an electricity meter that is hard to reach, which makes the process inefficient and reduces precision. This may result in billing issues or an interrupted power supply. Automating the electricity recharging process will eliminate the need for manual input, making it much more efficient and significantly improving accuracy. TekenToken is an innovation in the field of robotics designed to automate the process of electricity recharging through prepaid tokens. This system utilizes a Cartesian robot, which enables precise movement along the X, Y, and Z axes to press the buttons on the electricity meter. TekenToken also incorporates an IoT system using an online database like Firebase, connecting the system to a mobile application that allows for long-distance remote control. By implementing a flexible system such as a Cartesian robot and IoT, TekenToken can also be modified for application in many other fields.